(untitled) (Praxis Educativa, 2022)
Abstract: The teacher is responsible for putting into practice the curricular design of his/her disciplinary area; this implies a set of essential professional skills to evaluate, assess and choose the most appropriate model and pedagogical strategies. Obviously, this process implies a whole cultural baggage supported by the value structures themselves which are not neutral. In this sense, the present study aims to analyze the configuration of the axiological profiles of teachers and students of pedagogical careers, through the application of the PVQ-40 (Portrait Values Questionnaire) by Shalom Schwartz. We worked with an intentional sample, made up of 337 participants; of which, 95 (28.2%) had a professional teaching degree and 242 (71.8%) were teaching at different training institutes in the province of Mendoza-Argentina. In the results, significant differences can be seen in relation to sociodemographic variables, the type of administration of educational institutions and the assessment of the teaching career.